2016
DOI: 10.1091/mbc.e16-02-0116
|View full text |Cite
|
Sign up to set email alerts
|

Syndapin/SDPN-1 is required for endocytic recycling and endosomal actin association in theCaenorhabditis elegansintestine

Abstract: In vivo analysis of the F-BAR–domain protein syndapin indicates that it regulates basolateral recycling of transmembrane cargo in the Caenorhabditis elegans intestine. SDPN-1 may facilitate the fission of membranes from the early endosome that are acquiring recycling endosome characteristics, allowing cargo to exit the early endosome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 61 publications
0
38
0
Order By: Relevance
“…Our work indicates that microvillus inclusions originate from endocytosis and are dependent on dynamin and Pacsin 2. Interestingly, there is a single report in C. elegans intestine that Syndapin 1 is required for endocytic recycling (Gleason et al, 2016). This report demonstrated that Syndapin 1 was present in early and basolateral Moreover, Syndapin 1 deletion mutants exhibited decreased basolateral recycling transport and accumulation of endosomes positive for early endosome and recycling endosome markers (Gleason et al, 2016).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our work indicates that microvillus inclusions originate from endocytosis and are dependent on dynamin and Pacsin 2. Interestingly, there is a single report in C. elegans intestine that Syndapin 1 is required for endocytic recycling (Gleason et al, 2016). This report demonstrated that Syndapin 1 was present in early and basolateral Moreover, Syndapin 1 deletion mutants exhibited decreased basolateral recycling transport and accumulation of endosomes positive for early endosome and recycling endosome markers (Gleason et al, 2016).…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, there is a single report in C. elegans intestine that Syndapin 1 is required for endocytic recycling (Gleason et al, 2016). This report demonstrated that Syndapin 1 was present in early and basolateral Moreover, Syndapin 1 deletion mutants exhibited decreased basolateral recycling transport and accumulation of endosomes positive for early endosome and recycling endosome markers (Gleason et al, 2016). In mammals, the Pacsin 2 protein is primarily implicated in endocytosis, as it associates with multiple endocytic regulators including MICAL-L1, EHD1/mRme-1, and dynamin (Braun et al, 2005;Giridharan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…syndapin-1) and PACSIN2 (a.k.a. syndapin-II) (125)(126)(127) , ACAP1 44,128,129 and the SNX-BAR family [130][131][132][133][134] (see also Supplementary Table S1 for a list of membrane-remodelling protein and complexes currently implicated in endosomal recycling). BAR domains are α-helical coiled coils that dimerise to form a banana-shaped structure whose concave surface is lined with positively charged residues that mediate electrostatic interactions with the negatively charged membrane surface 135 (Figure 4).…”
Section: [H1] Tubular Transport Carrier Formationmentioning
confidence: 99%
“…Paradoxically, loss of EHS-1 leads to complete depletion of synaptic vesicles without apparent formation of endosomes, suggesting its function at the plasma membrane, while loss of ITSN-1 results in accumulation of large vesicles in the terminals (Salcini et al, 2001 ). The amphiphysin and syndapin homologs AMPH-1 and SDPN-1 act on early endosomes to regulate cargo recycling (Pant et al, 2009 ; Gleason et al, 2016 ). They are therefore not likely to be directly involved in synaptic vesicle endocytosis from the plasma membrane, although their exact roles are yet to be determined.…”
Section: Caenorhabditis Elegans Neuromuscular Junctionsmentioning
confidence: 99%